Design and Analysis of an Optical Coupler for Concentrated Solar Light Using Optical Fibers in Residential Buildings - Aslian, A.; Asli, B.H.S.; Tan, Chin Joo; Adikan, Faisal Rafiq Mahamd; Toloei, A. (Hindawi Publishing Corporation, 2016)
Concentrated sunlight that is transmitted by fiber optics has been used for generating electricity, heat, and daylight. On the other hand, multijunction photovoltaic cells provide high efficiency for generating electricity from highly concentrated sunlight. This study deals with designing and simulating a high-efficiency coupler, employing a mathematical model to connect sunlight with fiber optics for multiple applications. The coupler concentrates and distributes irradiated light from a primary concentrator. In this study, a parabolic dish was used as the primary concentrator, a coupler that contains nine components called a compound truncated pyramid and a cone (CTPC), all of which were mounted on a plate. The material of both the CTPC and the plate was BK7 optical glass. Fiber optics cables and multijunction photovoltaic cells were connected to the cylindrical part of the CTPC. The fibers would transmit the light to the building to provide heat and daylight, whereas multijunction photovoltaic cells generate electricity. Theoretical and simulation results showed high performance of the designed coupler. The efficiency of the coupler was as high as , whereas the rim angle of the dish increased to an optimum angle. Distributed sunlight in the coupler increased the flexibility and simplicity of the design, resulting in a system that provided concentrated electricity, heat, and lighting for residential buildings.